Qualidade de vida e sonolência diurna em pacientes com apneia obstrutiva do sono submetidos ao avanço maxilomandibular - Squarisi, José Mauro de Oliveira (2020)
Introduction: The maxillomandibular advancement (MMA) is considered the most effective surgical treatment for obstructive sleep apnea (OSA). However, its impact on the perception of physical and psychosocial well-being has been little studied. Purpose: To assess the quality of life related to health and excessive daytime sleepiness of patients diagnosed with moderate and severe OSA who underwent a MMA surgery. Method: Between February 2018 and February 2019, patients with moderate and severe OSA who had MMA surgery approximately one year before the study and patients in the preoperative period (control group) were invited to respond a self-applied questionnaire to assess their quality of life concerning health (Medical Outcomes Study 36-Item Short-Form Health Survey SF-36 and Functional Outcomes of Sleep Questionnaire – FOSQ) and a daytime sleepiness scale (Epworth Sleepiness Scale – ESE). We collected sociodemographic, clinical and polysomnographic data. Results: Twenty-two patients who underwent MMA surgery (average age = 48.1 years / SD = +- 7.77 years; body mass index (BMI) of 32.1 +- 3.7 kg/m2 and a preoperative apnea-hypopnea index (AHI) of 60.1 +- 25.5 episodes/hour) and twenty-eight patients in the preoperative period (average age = 43.0 years / SD = +- 10.26 years; BMI = 31.0 +- 4.6 kg/m2 and preoperative AHI = 60.0 +- 24.0 episodes/hour) participated in the study. Patients who underwent MMA presented less daytime sleepiness: 5.0 (3.00 – 8.00) versus 16.0 (9.00 – 21.00), p<0.01; better general quality of life in the domains physical functioning: 100.0 (50.00 – 100.00) versus 62.5 (0.00 – 100.00), p<0.05; vitality: 65.0 (58.75 – 90.00) versus 55.0 (21.25 – 67.50), p<0.01; mental health: 78.0 (67.00 – 88.00) versus 62.0 (45.00 – 75.,00), p<0.01; and social functioning: 88.0 (75.00 – 100.00) versus 69.0 (41.00 – 100.00), p<0.05; and better sleep-related quality of life in the domains general productivity: 4.00 (3.63 – 4.00) versus 2.9 (2.03 – 3.75), p<0.01; social outcomes: 4.00 (4.00 – 4.00) versus 3.2 (2.00 – 4.00), p<0.01; activity level: 3.7 (3.56 – 3.88) versus 2.8 (1.64 – 3.53), p<0.01; and vigilance: 3.9 (3.55 – 4.00) versus 2.7 (2.03 – 3.67), p<0.01 when compared to the control group. Conclusion: Our results suggest that patients with moderate and severe OSA undergoing MMA have a positive impact on quality of life and daytime sleepiness when compared to patients in the preoperative period.